Etnogeneze Slovanů: staré a nové otázky a spory - Michal Téra (Theatrum Historiae)
The ethnogenesis of the Slavs still belongs to the unresolved problems of contemporary science. In the past, a number of theories on the original Slavic homeland came into being. The first complex theory was introduced by Lubor Niederle, who located the original Slavic settlements in the territory around the Carpathian arc, between the Vistula and the Dnieper Rivers. Even nowadays, there are several theories. “The Vistula-Odra theory” looks for the original homeland of the Slavs in the territory of today’s Poland, and the roots of the Slavic ethnic group in the Lusatian and Przeworsk cultures. “The Dnieper theory” searches for the original Slavic region in Eastern Europe, on the Middle Dnieper, and the roots of the Slavic ethnogenesis in the Kiev and Zarubino cultures.